Positive Relationship Between Paroxysmal Vertigo and Right-to-Left Shunt: A Large Observational Study - Kaiming Liu; Xiulin Tian; Wenwu Hong; Yujin Xiao; Juanyan Chen; Haidi Jin; Faming Wang; Xiaopei Xu; Tao Zang; Liang Zhang; Mengxiong Pan; Xiaodong Zou (Frontiers in Neurology, 2022)
BackgroundThe association between paroxysmal vertigo and right-to-left shunt (RLS) is rarely reported. This study investigates the prevalence and correlation of RLS in patients with different paroxysmal vertigo diseases.MethodsPatients with paroxysmal vertigo from seven hospitals in China were included in this observational study between 2017 and 2021. Migraine patients within the same period were included for comparison. Demographic data and medical history were collected; contrast transthoracic echocardiography was performed; and the clinical features, Dizziness Handicap Inventory, and incidence of RLS in each group were recorded.ResultsA total of 2,751 patients were enrolled. This study's results demonstrated that the proportion of RLS in patients with benign recurrent vertigo (BRV) and vestibular migraine (VM) was significantly higher than that in patients with benign paroxysmal positional vertigo, Meniere's disease, and vestibular paroxysmia (P < 0.05). No statistical difference was shown between the frequency of RLS in patients with BRV and those with migraine and VM. A positive correlation was shown between the RLS grade and Dizziness Handicap Inventory scores of patients with VM and BRV (P < 0.01) after effectively controlleding the effect of confounding variables.ConclusionsRLS was significantly associated with BRV and VM. RLS may be involved in the pathogeneses of BRV and VM and may serve as a differential reference index for the paroxysmal vertigo.Trial RegistrationCHRS, NCT04939922, registered 14 June 2021- retrospectively registered, https://register.clinicaltrials.gov.